MANAGEMENT OF ISLAMIC BOARDING SCHOOL PROGRAMS IN CHARACTER FORMATION DURING SOCIETY 5.0 ERA AT MTS NEGERI 1KEBUMEN - Salim Wazdy; Tutuk Ningsih, Muhamad Slamet Yahya (Adisam Publisher, 2024)
In Indonesia, Islamic educational institutions offering boarding education extend beyond traditional pesantren. Currently, madrasahs have adopted boarding school systems referred to as Islamic Boarding School (IBS) programs. IBS is considered a viable solution to address the challenges of the modern era, serving as an alternative for parents seeking to provide their children with a strong religious education experience. This research employs a constructivist paradigm with a field research approach and a qualitative-descriptive method. The author utilizes observation, interviews, and documentation to collect and analyze data. The results indicate that the implementation of the IBS program in character formation during the Society 5.0 era at MTs Negeri 1 Kebumen is effective and efficient. This success is attributed to the managerial framework aligning with stages outlined in G. Terry's management theory, encompassing planning, organizing, executing, and monitoring